Does father–child conflict mediate the association between fathers' postnatal depressive symptoms and children's adjustment problems at 7 years old?. Issue 8 (11th March 2016) - Nath, S.; Russell, G.; Kuyken, W.; Psychogiou, L.; Ford, T.
Abstract : Background: Paternal depressive symptoms are associated with children's emotional and behavioural problems, which may be mediated by negative parenting. But there is no research on the influence of paternal depressive symptoms on children's emotion regulation and limited literature investigating fathers' parenting as a mediator in the pathway between paternal depressive symptoms and children's externalizing and internalizing problems. We aimed to investigate the mediating role of father–child conflict (at 3 years) in the association between postnatal paternal depressive symptoms (at 9 months) and children's emotional and behavioural problems (at 7 years) (aim 1). We also examined whether mediation pathways were more pronounced for boys or for girls (aim 2). Method: Secondary data analysis was conducted on the Millennium Cohort Study, when children were 9 months, 3 years and 7 years old ( n = 3520). Main study variables were measured by self-report questionnaires. Fathers completed the Rutter Scale (depressive symptoms) and the Parent–Child Relationship Questionnaire (father–child conflict), while mothers completed the Strengths and Difficulties Questionnaire and the Social Behaviour Questionnaire (child emotional and behavioural problems, emotion regulation). We used structural equation modelling to estimate direct, indirect and total effects of paternal depressive symptoms on child outcomes, mediated by father–child conflict whilst adjusting for relevant covariates (maternal depressive symptoms, child temperament, marital conflict, and socio-economic factors such as poverty indicator and fathers' education level). Multi-group and interaction analysis was then conducted to determine the differential effect by gender of the association between paternal depressive symptoms on child outcomes via father–child conflict. Results: Father–child conflict mediated the association between paternal depressive symptoms and emotion regulation problems [standardized indirect effect (SIE) 95% confidence interval (CI) −0.03 to −0.01, p < 0.001; standardized total effect (STE) 95% CI −0.05 to −0.01, p < 0.05] (aim 1). Father–child conflict mediated a larger proportion of the effect in boys (SIE 95% CI −0.03 to −0.01, p < 0.001; STE 95% CI −0.05 to 0.00, p = 0.063) than it did in girls (SIE 95% CI −0.02 to −0.01, p < 0.001; STE 95% CI −0.04 to 0.01, p = 0.216) (aim 2). Conclusions: Father–child conflict may mediate the association between postnatal paternal depressive symptoms and children's emotion regulation problems. Paternal depressive symptoms and father–child conflict resolution may be potential targets in preventative interventions.